2014
DOI: 10.1177/1535370214549518
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration produced by new mineralized and reticulated collagen membranes in critical-sized rat calvarial defects

Abstract: The aim of this study was to evaluate the bone regenerative effect of glutaraldehyde (GA) cross-linking on mineralized polyanionic collagen membranes in critical-sized defects on rat calvarias. Bone calvarial defects were induced in Wistar rats, which were then divided into five groups: a sham group; a control group, which received a commercial membrane; and GA, 25GA, and 75GA groups, which received one of three different polyanionic collagen membranes mineralized by 0, 25, or 75 hydroxyapatite cycles and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Treatment with XFZY attenuated this upregulation, suggesting that the neuroprotective effect of XFZY against TBI may involve functional improvement of the BBB. However, bone resorption after skull fracture also results in the release of collagens (Verissimo et al., 2015), causing an increase in trans -4-hydroxy-L-proline level. The decreased trans -4-hydroxy-L-proline induced by XFZY may also result from healing of the traumatic skull.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with XFZY attenuated this upregulation, suggesting that the neuroprotective effect of XFZY against TBI may involve functional improvement of the BBB. However, bone resorption after skull fracture also results in the release of collagens (Verissimo et al., 2015), causing an increase in trans -4-hydroxy-L-proline level. The decreased trans -4-hydroxy-L-proline induced by XFZY may also result from healing of the traumatic skull.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite‐incorporated membranes have been shown to promote the functional activity of stromal cells and osteoblast‐like cells in vitro (Table ) and induce bone formation in vivo , in combination with non‐resorbable (Table ) and resorbable (Table ) membranes. The HA powder used for preparation of pure ceramic membrane or other types of membrane has also been combined with bioactive ions, including strontium , silver , and zinc (Table ), to enhance their biological performance in vivo.…”
Section: Membrane Properties and Their Modificationsmentioning
confidence: 99%
“…Several studies have reported changes in mechanical properties and outcomes of GBR by adding additives to collagen membrane (Table 1). The percentage of new bone formation in (iii), (iv), and (v) was higher than (i) and (ii) • No significant difference in bone formation among (iii), (iv), and (v) [13] 5 mm Calvarial defect (rat) (i) Untreated collagen membranes (ii) EGCG cross-linked collagen membranes (iii) Nano-HA modified collagen membranes (iv) Nano-HA modified EGCG-collagen membranes…”
Section: Collagenmentioning
confidence: 85%
“…Collagen has been used as a resorbable membrane for GBR [11]. Collagen membrane has the advantages of low antigenicity, high biocompatibility, and excellent cell affinity, but pure collagen has the disadvantage of being difficult to handle due to a paucity of physical properties, and it is degraded quickly [12][13][14].…”
Section: Collagenmentioning
confidence: 99%
See 1 more Smart Citation